PENGARUH JIWA KEWIRAUSAHAAN DAN KREATIVITAS TERHADAP KEBERHASILAN USAHA PERCETAKAN DI KABUPATEN OGAN KOMERING ULU - Rika Fitriyani; Sally Maria Bramana; Evandry Deswana (STIE DWI SAKTI BATURAJA, 2022)
The aim of this research is to determine the effect of the entrepreneurial spirit and creativity on the success of the printing business in Ogan Komering Ulu Regency. The method used in this research is descriptive method. The results of the study obtained multiple linear regression equation Y = 8.925 + 0.287X1 + 0.303X2. The correlation value between the variable Entrepreneurial spirit (X1) and creativity (X2) on business success (Y) is 0.623, which means the correlation between the independent variables, namely the dependent variable, namely business success (Y) has a strong correlation. The t value of the entrepreneurial spirit (X1) has a tcount of 3.397 > ttable 2.02269, then Ho is rejected and Ha is accepted, which means that there is an influence of the entrepreneurial spirit (X1) on the success of the printing business in Ogan Komering Ulu Regency. The value of t arithmetic creativity (X2) tcount 2.506 > t table 2.02269 then Ho is rejected and Ha is accepted which means that there is an influence of creativity (X2) on the success of the printing business in Ogan Komering Ulu Regency. The results of the F test obtained that the value of Fcount 12.364 > Ftable 3.22 means that Ho is rejected and Ha is accepted. This means that there is an influence of entrepreneurial spirit (X1) and creativity (X2) on the success of the printing business in Ogan Komering Ulu Regency.